2010
DOI: 10.1186/1476-8518-8-6
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of Engystol® and Gripp-Heel®: an in-vitro assessment

Abstract: BackgroundInfections with respiratory viruses can activate the innate immune response - an important host defence mechanism in the early stage of viral infection. Interferon (IFN) release, triggered by virus infection, is an important factor in establishing an antiviral state, where IFN activation occurs prior to the onset of the adaptive immune response.The two ultra-low-dose combination medications, Engystol® and Gripp-Heel®, have documented efficacy for the treatment of the respiratory infections. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
(34 reference statements)
0
12
0
2
Order By: Relevance
“…In vitro, homeopathic remedies made from botanical sources demonstrate antiviral effects and the ability to stimulate patterns of change in pro- and anti-inflammatory cytokine release [183, 201, 202]. Even while dismissing the favorable findings, the otherwise negative (albeit highly flawed - [203205]) Shang et al’s metaanalysis reported a subanalysis of homeopathy efficacy studies restricted to infectious diseases that revealed a strongly significant benefit of homeopathic treatment [206].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro, homeopathic remedies made from botanical sources demonstrate antiviral effects and the ability to stimulate patterns of change in pro- and anti-inflammatory cytokine release [183, 201, 202]. Even while dismissing the favorable findings, the otherwise negative (albeit highly flawed - [203205]) Shang et al’s metaanalysis reported a subanalysis of homeopathy efficacy studies restricted to infectious diseases that revealed a strongly significant benefit of homeopathic treatment [206].…”
Section: Resultsmentioning
confidence: 99%
“…Previous empirical studies have shown that different homeopathic remedies modulate components of the allostatic stress response network. These findings include remedy-induced changes in heat shock proteins [7,17,146], cytokines [147-149], immune [150-153], metabolic [12,131], and nervous system [154-162] function, as well as gene expression patterns [9,163,164]. Nanoparticles per se can and do mobilize components of the allostatic network [165-167].…”
Section: Discussionmentioning
confidence: 99%
“…159,247249 Adaptive changes in allostasis initiated by low dose nanoparticles during homeopathic treatment could help restore more normal balance between pro- and anti-inflammatory cytokines, as suggested by previous studies. 6669,163,182,185,250–252 The result would be improvements of both psychological and physical well being across a wide range of conditions, as is claimed in hundreds of anecdotal case reports from homeopaths and supported by a number of observational trials. 253,254 …”
Section: The Net Clinical Outcome Of the Simillimum Remedy Interactiomentioning
confidence: 94%
“…The endogenous adaptations include multiple, interacting shifts in central nervous system function, 9,52,53 autonomic balance, 54 heat shock protein activation, 5557 cortisol release, 5865 inflammatory cytokine expression, 66,67 and/or immune system mobilization. 6870 A homeopath might describe the patient as “never having been well since” an adverse life event.…”
Section: Introductionmentioning
confidence: 99%